Study of Regional Disparities among Districts in East Java Province - Enggar Dwi Novianto; Wiwandari Handayani (Department of Urban and Regional Planning, Universitas Diponegoro, 2018)
Some evidences have emerged indicating that there are regional disparities in East Java Province and industrialization seems to give its contribution in creating regional disparities. In 2014, Manufacturing industry dominated the contribution to the GDP which was 29%, on the other hand mostly the people who worked in the agricultural sector, and so the land which mostly agricultural. This study aims to identify factors influencing the disparities in East Java Province. This statement is also strengthened by the Williamson index which showed that the regional disparities were quite high, with two districts indicated to contributing the most, Kediri and Surabaya City. By using factor analysis, this research will try to answer what factors influencing the disparities statistically, and cluster analysis is trying to figure out the disparities spatially. Then it is going to be proven that some districts agglomerated in a certain area and can implicate the disparities in East Java.